A Critique on the Book Measuring and Managing Organizational Culture Tools and Methods of Improvement - Alireza Banagar; Zahra Saeedi Ramiani; Nadi Alizadeh; Faranak Paydar (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of this article is to review and critique the book entitled Measuring and Managing Organizational Culture Tools and Methods for Improvement the Work of Mahdi Ebrahimi Blani, Vida Rashidi and Saeed Shahbazmoradi. This work has been written in the field of management and organizational culture and has been set up in four chapters and a preface. In the process of critique and evaluation of this book, the criteria and indicators of critique are used in accordance with the model provided by the Iranian council for reviewing books and text on human sciences. In this regard, this book is evaluated in terms of method and then in terms of content and structure. Also, book improvements are charged to enrich the book and opening the other fields of research. The result of studying this work showed that the authors of the book can increase the credibility of the work by observing the principles of reference in the expression of texts and tables and also by combining the work with Islamic texts and by structural and content review of the work can add to the richness of the work.